Equity and diversity in astronomy. (July 2018) - Jermak, Helen; Lucatello, Sara; Woods, Paul
'Why is there a black hole where women should be?' asked Member of Parliament Chi Onwurah during her plenary talk on women in science at EWASS 2018. Gender equity was among a variety of topics discussed in a day-long Special Session.